CYTOTOXICITY AND ANTIOXIDANT ACTIVITY OF ZINGIBER OFFICINALE AND 6-GINGEROL ON HEPG2 CELLS - Hanif, Harliansyah; Azian Murad, Noor; Wan Ngah, Wan Zurinah; Anum Mohd Yusof, Yasmin (Jurnal Kedokteran YARSI, 2008)
The present study was designed to compare the effects of ethanolic extract of ginger (Zingiber officinale) and its phenolic component [6]-Gingerol on viability, antiproliferation and apoptotic levels of human hepatoma cell lines (HepG2) and its antioxidant activity. HepG2 cells were cultured in Eagle?s minimum essential medium (EMEM) and the percentage of cell cytotoxicity was evaluated by tetrazolium salt (MTS) assay. Antiproliferation and apoptotic levels were measured by 5?Bromo-2?deoxyuridine (BrdU) colorimetry. Antioxidant capacity was studied by 1.1-diphenyl-2-picryl-hydrazyl radical (DPPH) using spectrophotometry. We found that cytotoxicity and antiproliferative effect of ginger extract and [6]-Gingerol could be associated with induction of apoptosis. The ginger ethanol extract and [6]-Gingerol also showed remarkable antioxidant activities in comparison with ascorbic acid and N-acetyl-L-cysteine.